A Review of Herbal Remedies for Multiple Sclerosis-Like Disorders in Traditional Persian Medicine (TPM) - Zarshenas, Mohammad M.; Ansari, Ramin; Dadbakhsh, Amirhossein; Mohammadi, Maryam (Current Drug Metabolism, 2018)
Background: Among various neurological disorders, multiple sclerosis (MS) is an expanding global immune- related inflammatory disease with complex etiologies. There is increasing demand for the use and administration of natural medicaments for this disorder. Traditional Persian Medicine (TPM) is a school of medicine and a medicinal plants-based resource for clinical studies put forward by Persian scholars. Objective: This paper aims to gather and study the effectiveness of all medicinal plants from the most popular Persian pharmacopeias. Five main Persian pharmacopeias from the 9th to the 18th century A.D. have been studied to identify the remedial plants for this disorder. Moreover, PubMed, and Scopus databases have been checked to derive relevant activities for these plants. Khaddar (numbness), Esterkha (Palsy) and Falej (quadriplegia) are traditional definitions; these are clinically close to what is known as MS in today's medicine. Conclusion: In all, 118 medicinal plants, related to 65 families, have been authenticated out of 157 chosen medicaments. Apiaceae is the most frequent family (13 reports). Fruits and roots of plants have been the most reported botanical parts (34 and 32 items). The employed routes of administration are topical, oral, or a combination of the two (27, 57, and 34 sequentially). Fifteen medicines have been reported for Khaddar, Esterkha, and Falej simultaneously. Antioxidant activities, immunomodulatory, and anti-inflammatory properties of medicines are known as some main mechanisms to manage MS. These functions are possessed by 81%, 36%, and 48% of the studied plants, respectively. Hence, conducting adducible clinical trials and highly approved experimental tests on animals may lead to novel drugs with lesser undesirable and much more therapeutic effects on controlling MS.
Keywords: herbal remedies